Classified [large type] - Michaels, Fern (Michaels, Fern. Godmothers, 2013)
Toots and Phil are ready to take their relationship to the next level, but after being widowed eight times, Toots is reluctant-- and she has other problems. Two young children, last seen in Toots's bakery, have gone missing. Finding the missing kids proves more complicated and dangerous than The Godmothers ever imagined.